Regarding the issue of the influence of factors on the braking parameters of M1 category vehicles with electric or hybrid power unit - Leontiev, Dmytro; Frolov, Andrii; Smetanin, German; Riabushko, Ivan; Леонтьєв, Дмитро Миколайович; Фролов, Андрій Анатолійович; Сметанін, Герман Володимирович; Рябушко, Іван Андрійович (Харківський національний автомобільно-дорожній університет, 2024)
Problem. The relevance of this work is explained by the fact that there are no works at all in the reference and normative literature on the theory and practice of forensic auto technical examination, and even more so, methodical recommendations regarding the values of the braking parameters of vehicles of the M1 category with an electric power plant. Goal. The purpose of the work is to establish the factors that affect the braking parameters of M1 category vehicles with an electric or hybrid power unit. Methodology. The approaches adopted in the work to solve the set goals are based on the theory of conducting the experiment, the theory of the interaction of the pneumatic tire with the road surface, the theory of the car and the laws of theoretical mechanics. Results. On the basis of the obtained experimental data regarding the value of permanent deceleration and the time value of the increasing deceleration during emergency braking of the M1 category vehicles with an electric or hybrid power unit, the tasks will be solved necessary for conducting forensic engineering and transport examinations for specific road traffic events with the participation of M1 category vehicles with an electric or hybrid power unit. Originality. The results of the study provided an opportunity to get an idea of the influence of factors on the braking parameters of M1 category vehicles with an electric or hybrid power unit. Practical value. The obtained results can be recommended to forensic experts when writing expert opinions or expert studies.
Щодо питання впливу факторів на параметри гальмування транспортних засобів категорії М1 з електричною або гібридною силовими установками
Keywords: all-terrain vehicle; transmissions of off-road vehicles; hydrostatic motor-wheels and pumps; traction-speed characteristics; transmission calculation; ефективність гальмування; електромобіль; транспортний засіб категорії М1; реалізоване зчеплення; коефіцієнт гальмування; уповільнення; 629.01; 10.30977/AT.2219-8342.2024.54.0.01